2013
DOI: 10.1186/1471-213x-13-37
|View full text |Cite|
|
Sign up to set email alerts
|

The dermomyotome ventrolateral lip is essential for the hypaxial myotome formation

Abstract: BackgroundThe myotome is the primitive skeletal muscle that forms within the embryonic metameric body wall. It can be subdivided into an epaxial and hypaxial domain. It has been shown that the formation of the epaxial myotome requires the dorsomedial lip of the dermomyotome (DML). Although the ventrolateral lip (VLL) of the dermomyotome is believed to be required for the formation of the hypaxial myotome, experimentally evidence for this statement still needs to be provided. Provision of such data would enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Myf5 expression was tightly associated with cells in the dorsomedial and ventrolateral lips of the dermomyotome and the associated sub-lip domains, which account for the incremental growth of the myotome (Kahane et al 1998a , 2007 ; Denetclaw & Ordahl, 2000 ; Pu et al 2013 ). However, the rostrocaudal lips are a further, important source of myogenic cells and are thought to drive the expansion of the myotomal centre (Kahane et al 1998a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myf5 expression was tightly associated with cells in the dorsomedial and ventrolateral lips of the dermomyotome and the associated sub-lip domains, which account for the incremental growth of the myotome (Kahane et al 1998a , 2007 ; Denetclaw & Ordahl, 2000 ; Pu et al 2013 ). However, the rostrocaudal lips are a further, important source of myogenic cells and are thought to drive the expansion of the myotomal centre (Kahane et al 1998a ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, cells from the dorsomedial lip of the dermomyotome detach and contribute to the myotome, thereby driving its dorsomedial outgrowth (Denetclaw et al 1997 ). With a slight delay, cells from the ventrolateral dermomyotomal lip engage in the same process, driving ventrolateral outgrowth (Kahane et al 1998a , 2007 ; Denetclaw & Ordahl, 2000 ; Pu et al 2013 ); the exception is found at limb levels where cells from the ventrolateral dermomyotomal lip emigrate to provide the limb musculature. Cells from the rostral and caudal lips also detach and intercalate into the existing scaffold, thereby driving the extension of the myotomal centre (Kahane et al 1998a ).…”
Section: Introductionmentioning
confidence: 99%
“…The myotome is a metameric series of muscles transiently present in all amniote embryos. Ultimately, the dorsomedial lip of the dermomyotome and the medial myotome give rise to the epaxial muscles, while the ventrolateral lip of the dermomyotome and the lateral myotome give rise to the hypaxial muscles (Figure 3A-C; Cinnamon et al, 1999; Denetclaw et al, 1997; Gros et al, 2004; Pu et al, 2013). On a molecular level, the transcription factor, Engrailed , appears to be essential for establishing the boundary between the epaxial and hypaxial muscle domains (Ahmed et al, 2017; Wotton et al, 2015).…”
Section: Axial Musclementioning
confidence: 99%
“…Progenitor cells that compose these somitic domains harbor distinct developmental potentials, with the sclerotome producing cartilaginous and osteoid tissues of the vertebral column, and the myotome producing skeletal muscle (Pang and Thompson, 2011). By contrast, dermomyotomal progenitors exhibit the greatest diversity in cell fates: they are responsible for establishing the myotome (Gros et al, 2004;Pu et al, 2013) and, beyond muscle, give rise to the dermis of the back, as well as adipocytes in several adipose depots (Atit et al, 2006;Lepper and Fan, 2010;Sanchez-Gurmaches and Guertin, 2014a,b;Seale et al, 2008;Sebo et al, 2018).…”
Section: An Introduction To Mesoderm Anatomy and Fatementioning
confidence: 99%